CUSTOMARY LEGAL PROTECTION FOR THE CANCELLATION OF NGADET CEREMONY FOR DAYAK KENYAH COUPLE - Yuniarsih; Radhitya, Atthyya; Rosdiana, Anita (Awang Long Law Review, 2024)
This study explores the Ngadet ceremony, a traditional wedding practice of the Dayak Kenyah community in East Kalimantan, Indonesia, symbolizing the union of two families through sacred customary rituals. Governed by strict customary laws, Ngadet incorporates symbolic elements such as tajau (jars), baing (traditional beads), lekok (traditional rings), uleng udeng (headgear), gongs, iron chains, seraung (traditional hats), and pat uwai (woven mats), each carrying deep cultural significance. The study adopts a socio-legal approach, focusing on the social and legal dimensions of Ngadet, including its stages, requirements, and the legal protections afforded to parties affected by its cancellation. Primary data were obtained through a direct interview conducted via WhatsApp with Mr. Yakub Ngau, the Customary Head of the Dayak Kenyah community in Makmur Jaya Village as a key informant. He provided accurate and detailed insights into the Ngadet tradition and the sanctions imposed in cases of cancellations. The findings reveal the Ngadet ceremony of the Dayak Kenyah Lepo’ Jalan tribe comprises three stages: pre-Ngadet (Mateb), involving preparations and offerings, the ceremony with symbolic rituals like processions, dances, and sacred items, and post-Ngadet, where the couple prepares for a church wedding to validate the marriage. Customary law imposes strict sanctions, including a Rp5,000,000 fine for cancellations, protecting women and reinforcing commitment through discussions, notifications, and mediation. In conclusion, the Ngadet ceremony, embodies unity, cultural heritage, and ancestral values. Governed by strict customary laws, it reinforces commitment and protects individuals through sanctions, ensuring the preservation of tradition.